DESIGNING PODCAST FOR STUDENTS: A PROTOTYPE FOR TEACHING ENGLISH IN LISTENING CLASS - Delsa Miranty; Dina Rachmawati (English Department - University of Sultan Ageng Tirtayasa, 2016)
In the context of language education, listening is recognized as the first skill that learnt by the students in the EFL classroom. However, some problems are commonly found in the process of learning to listen the material in form of English. Students are usually less confident and often confuse to start to listen the material in the EFL classroom. To minimize this problem, this study is aimed at discovering alternative tool in learning listening material by using Podcast. Four instruments were chosen to reveal students’ listening skill, they were: direct observation, questionnaire, interview and test. Direct observation was conducted three times, Likert Scale with five options was applied for questionnaires, close interview was conducted at the end of teaching learning process and the tests were conducted to check the students understanding of the materials. Moreover this research used one class in the third semester of English department in Untirta. The result of this research showed two things. First, there was effectiveness of using Podcast in the laboratory, since it has high score, for normalization gain score and the students finally had nice and good communication in the laboratory, the students have many time to download, listen, analysis and discuss the materials from Podcast with their team, out of the laboratory before they came to the laboratory. Second, there were good responses from the students since they got many advantages after using Podcast as the tool in the listening class, by applying podcast in the listening class. It started since the students were allowed to download, listen and give comments in the web blog about materials in critical listening from www.critical listening Podcast 2016.word press. Finally, by using Podcast, the English teacher also help the students to build their interaction skill and students’ self-confidence to improve their critical listening. Keywords: Critical Listening; EFL Classroom; Podcast